Effectiveness of Dunaliella salina Extracts against Bacillus subtilis and Bacterial Plant Pathogens - Alfredo Ambrico; Mario Trupo; Rosaria Magarelli; Roberto Balducchi; Angelo Ferraro; Evangelos Hristoforou; Tiziana Marino; Dino Musmarra; Patrizia Casella; Antonio Molino (Pathogens, 2020)
Several bacteria pathogens are responsible for plant diseases causing significant economic losses. The antibacterial activity of Dunaliella salina microalgae extracts were investigated in vitro and in vivo. First, biomass composition was chemically characterized and subjected to extraction using polar/non-polar solvents. The highest extraction yield was obtained using chloroform:methanol (1:1 v/v) equal to 170 mg g−1 followed by ethanol (88 mg g−1) and hexane (61 mg g−1). In vitro examination of hexane extracts of Dunaliella salina demonstrated antibacterial activity against all tested bacteria. The hexane extract showed the highest amount of β-carotene with respect to the others, so it was selected for subsequent analyses. In vivo studies were also carried out using hexane extracts of D. salina against Pseudomonas syringae pv. tomato and Pectobacterium carotovorum subsp. carotovorum on young tomato plants and fruits of tomato and zucchini, respectively. The treated young tomato plants exhibited a reduction of 65.7% incidence and 77.0% severity of bacterial speck spot disease. Similarly, a reduction of soft rot symptoms was observed in treated tomato and zucchini fruits with a disease incidence of 5.3% and 12.6% with respect to 90.6% and 100%, respectively, for the positive control.